182k views
2 votes
And evaluate x(- y + z) for x=-1 y=-2 and z=5

2 Answers

4 votes

Put the values of x, y and z to the expression.


(-1)(-(-2)+5)=(-1)(2+5)=(-1)(7)=-7

Used PEMDAS:

P Parentheses first

E Exponents (ie Powers and Square Roots, etc.)

MD Multiplication and Division (left-to-right)

AS Addition and Subtraction (left-to-right)

User Egga Hartung
by
7.3k points
4 votes
multiply x to (-y) then x to (z)
mean x(-y)+ x(z)
plug in the variable given
(-1)(-(-2)+5)
-2-5=-7
User Huskygrad
by
7.3k points